Looking Beyond the Horizon : A Case Study of PVH’s Commitment in Ethiopia’s Hawassa Industrial Park - Mihretu, Mamo; Llobet, Gabriela (World Bank, Washington, DC, 2017)
The story of how the PVH Corp. (referred to throughout this document as PVH) came to leada group of its top suppliers to build factories and a fabric mill in Ethiopia’s Hawassa IndustrialPark (HIP) is the study of a strong collaboration between a private company looking to optimizeits business model and a government aiming to transform its economy through global strategic repositioning. The success of this story hinges upon the intersection of their goals and a shared vision of development that includes a strong commitment to social and environmental goals.PVH was motivated to invest in Ethiopia to respond to shifts in the global apparel sector, its growing desire to retool its business model and to address its concerns about compliance with social and environmental standards in its traditional sourcing locations. PVH had decided to rethink its business model and to look beyond the horizon towards a new region in which tolocate its manufacturing base. To have better oversight and enforcement, PVH moved to adopta fully integrated vertical supply chain, including direct investment in one of the manufacturingfacilities.Key to Ethiopia’s success in attracting this important investor was the government’s ability and willingness to strategically evaluate its foreign direct investment (FDI) needs and strategy and to take steps to evolve into an attractive location for higher value-added export-oriented investment.This case study explains a private investor’s site selection process. It assesses the elements PVH prioritized when deciding to commit to Ethiopia, and specifically to HIP. The case study further assesses the government of Ethiopia’s strategy, level of readiness, interest, and commitment, and sets out some key challenges that lie ahead for this partnership. The case study is structured in ten sections. Section second offers a brief background on the textile and apparel industry, including an explanation of its value chain. It provides a brief corporate profile of PVH and its current global footprint and business model. Section third describes the site selection process: PVH´s initial explorations in Africa, its consideration of several African countries, and its initial conversations and negotiations with Ethiopian authorities. Section fourth discusses the Ethiopian government’s strategy to attract and expand export-oriented investments, including efforts to bolster the country’s competitiveness. This section attempts to offer some explanation why Ethiopia was the right fit at the right time and its level of readiness to land such an investment. It provides a brief profile of PVH’s Africa point of entry, the HIP. Section sixth covers the challenges that lie ahead for this-project---potential setbacks that will affect not only the consolidation and growth of the textiles and apparel industry in Ethiopia, but also the government’s vision of becoming the “manufacturing powerhouse of Africa.” Section eighth concludes with some key lessons from PVH’s decision to invest in Ethiopia. Such lessons may be relevant to countries or regions interested inattracting FDI and may be of particular interest to other African countries in their quest to attract major investments in the textile and apparel sector.